Effect of Red Betel Leaf (Piper crocatum) on Dam for Breast Milk Postpartum Mothers at Public Health Center of Jawilan - Iis Yulia; Retno Widowati; Shinta Novelia (Nursing and Health Sciences Journal (NHSJ), 2022)
Dam ASI (Air Susu Ibu) results from breast milk that is not immediately released and causes blockage of venous and lymphatic flow, most of which occur on the second to the tenth day of the puerperium. Based on a preliminary study conducted at the Jawilan Health Center UPT, data was obtained from January to June 2021 for postpartum mothers who experienced breast milk damming as many as 75 people. This study aims to analyze the effect of red betel leaf (Piper crocatum) on breast milk dams in postpartum mothers with a quasi-experimental design and a pre-test and post-test design with a control group. The sample in this study was 30 people. The instrument used the SPES checklist, and observations were carried out for four days, from the 7th to the 10th day after postpartum. The analysis used is the non-parametric Wilcoxon statistic test to test for differences in groups and the Mann-Whitney test to test differences between groups. The swelling score before and after the red betel compress on the 7th day is 5.53 and on the 10th day is 1.27. In the control group, the swelling score on the 7th day was 5.73, and on the 10th day was 2.53. In the in-group difference test, p<0.05, and the difference between groups, p<0.05. There was a significant decrease in swelling scores before and after giving red betel leaf to a postpartum mother's breast milk dam.